The comparative behaviour of apatite-zircon U-Pb systems in Apollo 14 breccias: implications for the thermal history of the Fra Mauro Formation - Nemchin, Alexander; Pidgeon, Robert; Healy, David; Grange, Marion; Whitehouse, M.; Vaughan, Jeffrey Patrick (Meteoritical Society, 2009)
We report secondary ion mass spectrometry (SIMS) U-Pb analyses of zircon and apatite from four breccia samples from the Apollo 14 landing site. The zircon and apatite grains occur as cogenetic minerals in lithic clasts in two of the breccias and as unrelated mineral clasts in the matrices of the other two. SIMS U-Pb analyses show that the ages of zircon grains range from 4023 ± 24 Ma to 4342 ± 5 Ma, whereas all apatite grains define an isochron corresponding to an age of 3926 ± 3 Ma. The disparity in the ages of cogenetic apatite and zircon demonstrates that the apatite U-Pb systems have been completely reset at 3926 ± 3 Ma, whereas the U-Pb system of zircon has not been noticeably disturbed at this time. The apatite U-Pb age is slightly older than the ages determined by other methods on Apollo 14 materials highlighting need to reconcile decay constants used for the U-Pb, Ar-Ar and Rb-Sr systems. We interpret the apatite age as a time of formation of the Fra Mauro Formation. If the interpretation of this Formation as an Imbrium ejecta is correct, apatite also determines the timing of Imbrium impact. The contrast in the Pb loss behavior of apatite and zircon places constraints on the temperature history of the Apollo 14 breccias and we estimate, from the experimentally determined Pb diffusion constants and an approximation of the original depth of the excavated samples in the Fra Mauro Formation, that the breccias experienced an initial temperature of about 1300-1100 C, but cooled within the first five to ten years.